Risk-Return Trade-off: Suspicious Effect of Skewness -An Empirical study of Chinese Firms - Bi, Yue (2013)
Enlightened by Henkel (2000, 2008), the reported research focuses on examine the effect of skewed return distribution on the inverse risk return relationship. This study will be based on empirical data of Chinese listed firms from 1999-2012. It is found that the distribution of ROA is left-skewed in most of the time periods and the extent of the skewness could influence the slope of the risk return association. To rotate the skewness effect, median is used instead of the mean. After correcting the skewness effect, it is found that rather than being the sole explanation of the inverse risk relationship, it would be more appropriate to suggest taking skewness into consideration while using other behavioral theories. Additionally I found that in Chinese market, the performance and the risk-seeking behavior of state-controlled companies are more conservative in time of economy booming and moderate in time of economic downturn.